(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
The aim of this paper is to analyse the key role played by Johnny Dorelli in the Italian erotic comedy of the 70s. With a transversal perspective, the essay focuses on Dorelli’s television shows hosted in the 60s and on his performances on the big screen, more specifically in Pasquale Festa Campanile’s films. “Come perdere una moglie... e trovare un’amante” and “Giorgio”, Dorelli’s LP which contains part of the soundtrack, will be used as a specific case study and also as a peculiar landmark in actor-singer’s artistic life.